Optimizing the mix design of cold bitumen emulsion mixtures using response surface methodology - Nassar, Ahmed I.; Thom, Nicholas; Parry, Tony (Elsevier, 2016)
Cold mix asphalt (CMA) has been increasingly recognized as an important alternative worldwide. One of the common types of CMA is cold bitumen emulsion mixture (CBEM). In the present study, the optimization of CBEM has been investigated, to determine optimum proportions to gain suitable levels of both mechanical and volumetric properties. A central composite design (CCD) with response surface methodology (RSM) was applied to optimize the mix design parameters, namely bitumen emulsion content (BEC), pre-wetting water content (PWC) and curing temperature (CT). This work aimed to investigate the interaction effect between these parameters on the mechanical and volumetric properties of CBEMs. The indirect tensile stiffness modulus (ITSM) and indirect tensile strength (ITS) tests were performed to obtain the mechanical response while air voids and dry density were measured to obtain volumetric responses. The results indicate that the interaction of BEC, PWC and CT influences the mechanical properties of CBEM. However, the PWC tended to influence the volumetric properties more significantly than BEC. The individual effects of BEC and PWC are important, rather than simply total fluid content which is used in conventional mix design method. Also, the results show only limited variation in optimum mix design proportions (BEC and PWC) over a range of CT from 10oC to 30oC. The variation range for optimum BEC was 0.42% and 0.20% for PWC. Furthermore, the experimental results for the optimum mix design were corresponded well with model predictions. It was concluded that optimization using RSM is an effective approach for mix design of CBEMs.